2013
DOI: 10.4238/2013.august.12.6
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of conserved vaccine targets in Streptococcus agalactiae strains isolated from fish, cattle, and human samples

Abstract: ABSTRACT. Streptococcus agalactiae (Lancefield group B; group B streptococci) is a major pathogen that causes meningoencephalitis Effective vaccines against the different serotypes or genotypes of pathogenic strains from the various hosts would be useful. We used an in silico strategy to identify conserved vaccine candidates in 15 genomes of group B streptococci strains isolated from human, bovine, and fish samples. The degree of conservation, subcellular localization, and immunogenic potential of S. agalactia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Bioinformatic analyses of Sip reveal that there is a signal peptide at the N-terminus, followed by a LysM petidoglycan interaction domain. The phylogenetic relationship of Sip in GBS isolates shows that Sip has a high homology in humans, bovines and tilapia [15]. The whole Sip of GBS isolated from humans and bovines was expressed successfully in BL21(DE3) transformed with pET32a-sip [12,27]; but when the BL21 (DE3) host was used in conjunction with pET vectors, some toxic proteins could not be successfully reproduced [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analyses of Sip reveal that there is a signal peptide at the N-terminus, followed by a LysM petidoglycan interaction domain. The phylogenetic relationship of Sip in GBS isolates shows that Sip has a high homology in humans, bovines and tilapia [15]. The whole Sip of GBS isolated from humans and bovines was expressed successfully in BL21(DE3) transformed with pET32a-sip [12,27]; but when the BL21 (DE3) host was used in conjunction with pET vectors, some toxic proteins could not be successfully reproduced [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sip is an attractive protein for a GBS serotype independent subunit vaccine because it is the only protective protein in the core genome and has been isolated in fish, cattle, and human [13][14][15]. This protein also protects mice against GBS isolated from humans and cattle [12,16,17].…”
Section: Introductionmentioning
confidence: 97%
“…The Vaxign execution pipeline is able to predict antigen cellular localization, adhesion, epitope binding to MHC class I and class II, and sequence similarities to human, mouse and/or pig proteins. Vaxign has successfully been tested in prediction of vaccine candidates for many different pathogens such as Brucella [5-7] , uropathogenic E. coli [4], Francisella [8], Streptococcus agalactiae [9] and human herpes simplex virus [10]. The experimental verification of Vaxign-predicted results [7] confirms the accuracy of the Vaxign vaccine candidate prediction.…”
Section: Progresses and Challengesmentioning
confidence: 94%
“…The underlying reasons for this general tendency of the terrestrial isolates to cause higher mortality in P1 and P2 compared to the piscine isolates are still unclear. However, recent studies have shown that some of the major virulence factors found in human and bovine isolates are absent from the ST260-261 GBS piscine lineages (Delannoy et al, 2013;Pereira et al, 2013b;Rosinski-Chupin et al, 2013). This needs to be confirmed in our collection of Australian ST-261 piscine isolates that have been used in this study.…”
Section: Phagocytosis and Downstream Cellular Antimicrobial Response mentioning
confidence: 99%
“…Comparison of the bacterial pan-genome of different strains isolated from different animals can revealed conserved antigen targets than can be used to better inform during bacterial vaccine design (Maione et al, 2005;Pereira et al, 2013b;Schubert-Unkmeir and Christodoulides, 2013;Tettelin, 2009). …”
Section: Advent Of the Latest Next Generation Sequencing (Ngs) Technomentioning
confidence: 99%